Principles of Corporate Governance G20/ОоECD as a Ground for the Introduction of the “Travel-Compliance” System - A. V. Shashkova (Московский журнал международного права, 2017)
The aim of the present Article is to analyze the impact of the Principles of Corporate Governance G20 / ОECD on the system of the effective corporate governance in the area of travel-compliance. Travel-compliance is a particularity of the compliance system, which has come to Russia recently. It is mainly used by large-scale corporations. The present article gives an example of Daimler AG and other companies to show the effectiveness of compliance in case of introduction of travel policies to the compliance policy of corporations and their strict execution by the employees. The author researches in detail practical application of the Principle I of the document for the economic effectiveness at the level of particular corporations. Another result of the present Article is in the substantiation by the author of the conclusion that application of the Principles of Corporate Governance G20 / ОECD at the level of particular corporations represents a good means of counter fighting corporate corruption, execution of the legal and ethic aspects of compliance, minimization of risks and complete compliance with the laws. General, specific and particular research methods are used in the Article, including systemic, comparative, historical and juridical research methods. The practical value of the article is in the possibility to apply its main provisions and results in scientific and academic activities while discussing questions on application of the Principles of Corporate Governance G20 / ОECD and Compliance system is general and Travel-Compliance system in particular.